Reduced Emissions and Enhanced Adaptation in Agricultural Landscapes - Fernandes, Erick; Thapa, Dipti; Madhvani, Sonia (World Bank, Washington, DC, 2012)
This brief is based on the key messages of a conference held on January 23, 2009 at the World Bank to review the state of the art on 'agriculture and climate change, investing now for a productive and resilient future.' It is not the formal position of any one academic institute or organization, but sets out the key issues on: a) carbon as an integral part of sustainable land, water and biodiversity management in developing country agricultural landscapes and in any post-2012 framework and market mechanisms. Agricultural emissions reductions are already eligible under the Kyoto mechanisms for annex one (industrialized) countries; b) agricultural soil carbon measurement, modeling, and monitoring capabilities; c) challenges and opportunities in estimating soil carbon stocks and changes; d) a robust and integrated measurement and monitoring system; and e) further action steps to ensure objective consideration of agricultural soil carbon in post-2012 climate change solutions.